A Bibliometric Mapping of mHealth Application in University Mental Health Policy and Practice - Ana Pujianti Harahap; Dina Lusiana Setyowati; Risza Choirunissa; Bintang Agustina Pratiwi; Noor Azizah; Adelina Pratiwi (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Mental health issues among university students are becoming increasingly prevalent and have a significant impact on academic performance and overall well-being. In response, mobile health (mHealth) applications and digital psychometric tools have emerged as promising solutions for expanding access to mental health support. However, challenges remain in terms of effectiveness, user engagement, long-term scalability, and integration into institutional frameworks and policy systems. Methods: This study conducts a comprehensive bibliometric analysis using three established techniques co-citation analysis, bibliographic coupling, and co-word analysis to examine the evolution of digital mental health research in higher education. These complementary methods collectively provide a triangulated understanding of intellectual foundations, thematic development, and conceptual trends. Data were retrieved from the Scopus database, filtered for relevance, and visualized using VOSviewer software to identify key themes, conceptual structures, and research trends. Results: The analysis identified four major co-citation clusters centered on psychometric tools and digital intervention strategies, three bibliographic coupling clusters highlighting challenges in engagement and implementation, and five Co-word clusters representing emerging research areas such as mindfulness apps, resilience, and digital literacy. Findings reveal growing interdisciplinary collaboration, yet highlight persistent barriers in user adherence, cultural adaptation, and policy development. Conclusion: The study provides a structured overview of current research on digital mental health interventions in higher education, uncovering gaps in policy integration and long-term effectiveness. It offers practical insights for educators, healthcare professionals, and policymakers seeking to develop sustainable, evidence-based mental health strategies. Moving forward, institutions must focus on inclusive design, ethical data use, and institutional readiness to enhance the impact and scalability of digital mental health tools.